Sphingomyelin-Based Nanosystems (SNs) for the Development of Anticancer miRNA Therapeutics - Surasa Nagachinta; Belen Lopez Bouzo; Abi Judit Vazquez-Rios; Rafael Lopez; Maria de la Fuente (Pharmaceutics, 2020)
Gene replacement therapy with oncosuppressor microRNAs (miRNAs) is a promising alternative to interfere with cancer progression. However, miRNAs are highly inefficient in a biological environment, hampering a successful translation to clinics. Nanotechnology can tackle this drawback by providing delivery systems able to efficiently deliver them to cancer cells. Thus, the objective of this work was to develop biocompatible nanosystems based on sphingomyelin (SM) for the intracellular delivery of miRNAs to colorectal cancer cells. We pursued two different approaches to select the most appropriate composition for miRNA delivery. On the one hand, we prepared sphingomyelin-based nanosystems (SNs) that incorporate the cationic lipid stearylamine (ST) to support the association of miRNA by the establishment of electrostatic interactions (SNs−ST). On the other hand, the cationic surfactant (DOTAP) was used to preform lipidic complexes with miRNA (Lpx), which were further encapsulated into SNs (SNs-Lpx). Restitution of miRNA145 levels after transfection with SNs-Lpx was related to the strongest anticancer effect in terms of tumor proliferation, colony forming, and migration capacity assays. Altogether, our results suggest that SNs have the potential for miRNA delivery to develop innovative anticancer therapies.